83 The use of virtual patients in education and assessment of postgraduate general surgical trainees – a pancreatic cancer model. (17th November 2016) - Walker, NR; Bamford, R; Alder, D; Duncan, P; Butcher, K
Abstract : Introduction: Virtual patients (VP) are a valuable method of e-learning and assessment of competencies, particularly clinical decision making. Using the Low-Fidelity method of VP design, a peer-reviewed VP was created and its value assessed to surgical trainees regarding decision-making in a safe environment. Methods: A VP was created based on the case of a 65 year old male with an undiagnosed pancreatic head adenocarcinoma. Decision making spanned from the patient's initial GP referral through to palliative care involvement. The map was synthesised using specific mind-mapping software and placed into Adobe Captivate, creating a fully interactive VP. Film production of the scenarios using a professional actor and make-up artist facilitated a realistic environment. At three intervals during the development, focus groups comprising of surgical trainees of varying levels including a hepatobiliary fellow critiqued the VP, focusing on accuracy, fidelity and value of the decision stems. Results: All trainees found the VP valuable and found the decision making challenging and rewarding. They identified the freedom to make the "wrong" decision and manage the consequences a valuable process for learning and that feedback was essential. They reported that the scenario was realistic and suggested supportive clinical supervision would increase fidelity. The fellows found the VP of most value as they would soon be making decisions as Consultants. All trainees identified they would like more access to VPs and agreed they would use regularly. The fellows were vital for identifying clinical inaccuracies and ensuring the data was up to date. Conclusions: Surgical trainees find VPs useful and would like more exposure to them. It was found that our VP is potentially useful for decision-making and assessment. Despite being in its initial stages, our intention is to incorporate the VP into the assessment process of general surgical trainees, revolutionising their assessment currently in the UK.